DAMPAK SUB-SEKTOR UNGGULAN TERHADAP PEREKONOMIAN KOTA SAMARINDA: PENDEKATAN INPUT-OUTPUT - Mahakam, Jerry Pahlevy; Michael, Michael; Amalia, Siti (Journal of Innovation in Business and Economics, 2015)
In this paper, the writer would like to investigate the sub-sectors of the economy categorized as superior, potential, and non-superior, determine the magnitude of  multiplier income arising from these sub-sector on household income and job opportunities, and identify the sub-sector of the economy which can be placed as a superior in Samarinda. This study employed Input-Output approach which later discovered several factors which were considered as superior, namely  food and beverage industry; Paper and printing industry; electricity; construction / building; land transportation; and other services, while the sub-sectors which were included in non-superior categories were rice, cassava, vegetables, fruits, other staple food crops, plantation crops, timber and forest products, fisheries, mining, timber industry, chemical industry, hotels, telecommunications, insurance, government, education services. In addition, the results of forward and backward linkages analysis and multiplier income calculating of household income and job opportunities found that those sub-sectors of food and beverage industry, building/ construction, other services, and land transportation were categorized into major sub-sectors.